From Waste to Resource : Shifting Paradigms for Smarter Wastewater Interventions in Latin America and the Caribbean - Rodriguez, Diego J.; Serrano, Hector Alexander; Delgado, Anna; Nolasco, Daniel; Saltiel, Gustavo (World Bank, Washington, DC, 2020)
Resource recovery from wastewater facilities in the form of energy, reusable water, biosolids, and other resources, such as nutrients, represents an economic and financial benefit that contributes to the sustainability of water supply and sanitation systems and the water utilities operating them. Resource recovery can transform sanitation from a costly service to one that is self-sustaining and adds value to the economy. Indeed, if financial returns can cover operation and maintenance costs partially or fully, improved wastewater management offers a double value proposition. This report summarizes the work of the World Bank's initiative "Wastewater: From Waste to Resource," launched to raise awareness among decision makers regarding the potential of wastewater as a resource. The report highlights the findings and conclusions from technical background reports, from an in-depth analysis of several case studies, and from the feedback received during workshops and seminars with main stakeholders.